2021
DOI: 10.1002/ptr.7096
|View full text |Cite
|
Sign up to set email alerts
|

The effects and mechanisms of aloe‐emodin on reversing adriamycin‐induced resistance of MCF‐7/ADR cells

Abstract: Multidrug resistance (MDR) is one of the major obstacles for clinical effective chemotherapy. In this study, the effects and possible mechanisms of aloe-emodin (AE) were investigated on reversing the adriamycin (ADR)-induced resistance of MCF-7/ADR cells. AE could significantly reverse the ADR resistance in MCF-7/ADR cells. The combination of AE (20 μM) and ADR had no effect on the P-glycoprotein (P-gp) level, but notably promoted the accumulation of ADR in drug-resistant cells. The efflux function of P-gp req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Emodin plays an important role in inducing cell cycle arrest in a variety of cancer cells. Cheng et al reported that aloe-emodin can strengthen the sensitivity of adriamycin to breast cancer cell by inhibiting G2/M phase, inducing apoptosis through DNA damage, ROS accumulation, and caspase-3 activation [ 29 ]. Dong et al found that emodin exerts inhibitory effects on the proliferation of HCC cells through restraint of S and G2/M phases [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emodin plays an important role in inducing cell cycle arrest in a variety of cancer cells. Cheng et al reported that aloe-emodin can strengthen the sensitivity of adriamycin to breast cancer cell by inhibiting G2/M phase, inducing apoptosis through DNA damage, ROS accumulation, and caspase-3 activation [ 29 ]. Dong et al found that emodin exerts inhibitory effects on the proliferation of HCC cells through restraint of S and G2/M phases [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al. presented that AE sensitized tumor cells to chemotherapeutic agents, indicating the potential of AE for improving drug resistance ( 18 ). In this study, AE could improve the drug resistance of PC9-GR cells and xenograft models.…”
Section: Discussionmentioning
confidence: 99%
“…Dou et al reported that AE could alleviate renal fibrosis by repressing PI3K/Akt/mTOR signaling pathway both in vivo and in vitro ( 17 ). Additionally, it has been demonstrated that AE could mitigate drug resistance of breast cancer cells and melanoma cells, indicating a regulatory role of AE in drug resistance ( 18 , 19 ). Nonetheless, effects of AE on drug resistance of NSCLCs have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Cheng et al found that AE also enhanced protective autophagy in reversing ADM-induced drug resistance. By supplementing AE with autophagy inhibitors, anti-tumor activity and sensibility may be enhanced (in vitro: MCF-7/ADR cell line, 20 μM, 48 h) [ 109 ].…”
Section: Natural Products Overcome Autophagy-mediated Tumor Drug Resi...mentioning
confidence: 99%